GEOCHEMICAL CHARACTERISTICS OF MAFIC DIKE ROCKS FROM THE SØR RONDANE MOUNTAINS, EAST ANTARCTICA - イケダ, ヤスオ; シライシ, カズユキ; カガミ, ヒロオ; IKEDA, Yasuo; SHIRAISHI, Kazuyuki; KAGAMI, Hiroo (National Institute of Polar Research, 1995)
P(論文) Mafic dike rocks (lamprophyre and dolerite) which have been metamorphosed up to amphibolite facies grade intruded Neoproterozoic metamorphic terrains of the Sør Rondane Mountains. Major and trace element abundance and Sr and Nd isotopic compositions were determined on the mafic dike rocks. The lamprophyre are characterized by extremely high K_2O, P_2O_5,Rb, Ba, Sr, Zr, and light rare earth elements which have minette or lamproite affinity. The geochemical characteristics of lamprophyre and dolerite suggest that these mafic rocks were derived from partial melting of a re-enriched mantle source by mixing of remnant subduction-related materials in the Pan-African orogenic time and a metasomatically enriched mantle. It seems likely that these mafic magmatic activities were related to post orogenic igneous activity in a continental collision zone linked to the Pan-African orogeny. departmental bulletin paper